G Gambaran Pengetahuan Perawat Tentang Metode ESI (Emergency Severity Index) DI Ruang Instalasi Gawat Darurat RSUD X - muthmainnah muthmainnah muthmainnah (LPPM Universitas Sari Mulia, 2022)
Background: The problem that is often encountered in hospitals is that many patients are given actions that are not in accordance with the emergency criteria and priority policies that must be handled by nurses, so that it can cause overcrowding. Meanwhile, emergency room services require fast and precise services. One of them is the ESI triage (Emergency Severity Index) which is currently being implemented in America with the advantage of faster, more precise patient identification and without the need to wait for a triage doctor. Objective: The purpose of this study was to identify a description of the level of knowledge of nurses about the ESI method. Method: This research method uses descriptive with total sampling technique. The research sample is 35 nurses who work in the emergency room of RSUD X and data collection is done using a questionnaire sheet. Result: The results obtained were that the majority of ER nurses had a good level of knowledge. Most of the ER nurses at RSUD X are 27-37 years old with a good level of knowledge, nurses are highly educated S1 and D3 Nursing, most of the sexes of nurses are male, most of the length of work carried out by nurses is fast (7 hours) and good knowledge who attend training. Conclusion: The conclusion of this study is that the level of knowledge of nurses is good about triage. Suggestions for nurses, who still do not understand ESI, to attend training and better understand how it is applied.